A Long Lifetime Aqueous Organic Solar Flow Battery. Issue 31 (8th July 2019) - Li, Wenjie; Kerr, Emily; Goulet, Marc‐Antoni; Fu, Hui‐Chun; Zhao, Yuzhou; Yang, Ying; Veyssal, Atilla; He, Jr‐Hau; Gordon, Roy G.; Aziz, Michael J.; Jin, Song
Abstract: Monolithically integrated solar flow batteries (SFBs) hold promise as compact stand‐alone energy systems for off‐grid solar electrification. Although considerable research is devoted to studying and improving the round‐trip efficiency of SFBs, little attention is paid to the device lifetime. Herein, a neutral pH aqueous electrolyte SFB with robust organic redox couples and inexpensive silicon‐based photoelectrodes is demonstrated. Enabled by the excellent stability of both electrolytes and protected photoelectrodes, this SFB device exhibits not only unprecedented stable continuous cycling performance over 200 h but also a capacity utilization rate higher than 80%. Moreover, through comprehensive study on the working mechanisms of SFBs, a new theory based on instantaneous solar‐to‐output electricity efficiency toward more optimized device design is developed and a significantly improved solar‐to‐output electricity efficiency of 5.4% from single‐junction silicon photoelectrodes is realized. The design principles presented in this work for extending device lifetime and boosting round trip energy efficiency will make SFBs more competitive for off‐grid applications. Abstract : Monolithically integrated solar flow batteries (SFBs) hold promise as compact stand‐alone systems for off‐grid solar electrification. Herein, a long lifetime neutral pH aqueous electrolyte SFB with robust organic redox couples and inexpensive silicon‐based photoelectrodes is demonstrated. The design principles presented herein for extending device lifetime and boosting round trip energy efficiency will make SFBs more competitive for powering off‐grid applications.